Of the Philosophy of Debt : In Search of the Relationship Between Debts and Duties - Stefanutti, Sarah (Scenari, 2021)
In spite of the historical and conceptual importance of the nexus between debt and morality, the relationship between debts and duties in particular, and the philosophy of debt in general, have been largely neglected in the discipline’s debate. This paper intends to be a first attempt to fill this research gap by addressing two fundamental questions, namely, what does it mean to think of moral duties as monetary debts? And, if we think of moral duties as debts, is this desirable? I will develop an answer by looking at how Kant and Nietzsche have discussed debt in relation to different types of obligations—individual and collective, private and political. Both Kant and Nietzsche broadly argue that debts must be understood as essential moral duties, and see debt-repayment as the quintssential moral ought, but this leads to diverging positions with regard to the desirability of conceptualizing duties as debts. On the ground that the creditor-debtor relationship is unjust, Nietzsche rejects all morality. While on the assumption that repaying one’s debts is a categorical imperative, Kant fails to question the injustices linked to debt-repayment.